Myringotomy and insertion of grommets as day surgery: a case study. (11th February 2021) - Daly, Michelle; Howe, Rachel
Abstract : This evidence-based case study follows a child from a nursing assessment on the day of his elective surgery at a children's hospital for myringotomy and insertion of grommets under general anaesthesia through to his arrival at the operating room. Potential pre-operative problems are identified and two problems that arose are discussed in detail. The main care provider in this case was a student nurse referred to as 'the nurse', supported by a qualified nurse, referred to as the 'registered nurse', who performed some assessments.